2021
DOI: 10.1088/1361-6668/abee2b
|View full text |Cite
|
Sign up to set email alerts
|

Topical Review: Multifilamentary coated conductors for ultra-high magnetic field applications

Abstract: High-temperature superconducting coated conductors (CCs) are considered an enabling ultra-high field (UHF) tape-conductor technology due to their extremely high engineering current densities at very high magnetic fields and low temperatures, and high mechanical strength. A major challenge is however related to induction of problematically large superconducting screening currents (as an effect of the large width-to-thickness ratio) when the wide tape conductors are exposed to strong transverse magnetic fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 170 publications
0
23
0
Order By: Relevance
“…High-temperature superconductor YBa 2 Cu 3 O 6+x (YBCO) thin films and coated conductors hold great potential for a variety of power applications, energy storage, high-speed computing etc [1][2][3][4][5], but to realize their full capability, the overall critical current density (J c ) needs to be maximized [6,7]. Since the thermal excitation of Cooper pairs and the field strength dependent Meissner effect greatly affect the J c , it is essential to design specific structures for various applications operating at different temperatures and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature superconductor YBa 2 Cu 3 O 6+x (YBCO) thin films and coated conductors hold great potential for a variety of power applications, energy storage, high-speed computing etc [1][2][3][4][5], but to realize their full capability, the overall critical current density (J c ) needs to be maximized [6,7]. Since the thermal excitation of Cooper pairs and the field strength dependent Meissner effect greatly affect the J c , it is essential to design specific structures for various applications operating at different temperatures and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the high field insert coil technology represents a crucial approach to achieving a stable state of strong magnetic field condition. Numerous fully superconducting magnets worldwide adopt the configuration of high-temperature superconducting coils inserted into lowtemperature superconducting magnets [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improvements in high-field magnets arising from the use of CCs, the screening current associated with the variation of the transverse magnetic field constitutes a major problem in practical magnets. Experiments and modeling [13][14][15][16][17][18] have shown that the screening current plays a role in reducing the total magnetic field and creating field spatial distortion. Furthermore, the decay of the screening current with time can lead to a temporal drift issue in the magnetic field due to thermally induced flux creep [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and modeling [13][14][15][16][17][18] have shown that the screening current plays a role in reducing the total magnetic field and creating field spatial distortion. Furthermore, the decay of the screening current with time can lead to a temporal drift issue in the magnetic field due to thermally induced flux creep [17,19,20]. All these effects are detrimental to the performance of NMR magnets [17,21].…”
Section: Introductionmentioning
confidence: 99%